2020
DOI: 10.1186/s13073-020-00781-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new driver and passenger mutations within APOBEC-induced hotspot mutations in bladder cancer

Abstract: Background APOBEC-driven mutagenesis and functional positive selection of mutated genes may synergistically drive the higher frequency of some hotspot driver mutations compared to other mutations within the same gene, as we reported for FGFR3 S249C. Only a few APOBEC-associated driver hotspot mutations have been identified in bladder cancer (BCa). Here, we systematically looked for and characterised APOBEC-associated hotspots in BCa. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 83 publications
(137 reference statements)
2
72
1
Order By: Relevance
“…At the present time no significant difference has been found in local relapse-free survival between bladder tumour subtypes in MIBC patients treated by TURBT followed by CCRT [44] or RT alone [45]. [36]); (b) cell line subtypes used in experimental studies of RT in BCa in vitro (classified by [46]); (c) cell line subtypes used in preclinical studies of radiotherapy in BCa in vivo (mice xenografts) (classified by [46]).…”
Section: Bca Tumour Subtypesmentioning
confidence: 67%
See 3 more Smart Citations
“…At the present time no significant difference has been found in local relapse-free survival between bladder tumour subtypes in MIBC patients treated by TURBT followed by CCRT [44] or RT alone [45]. [36]); (b) cell line subtypes used in experimental studies of RT in BCa in vitro (classified by [46]); (c) cell line subtypes used in preclinical studies of radiotherapy in BCa in vivo (mice xenografts) (classified by [46]).…”
Section: Bca Tumour Subtypesmentioning
confidence: 67%
“…Then, Earl et al assigned the subtypes to a series of 40 BCa cell lines [ 47 ]. Our group has made more stringent classification [ 46 ] For example, five cell lines discussed in this review were identified as “basal” by Earl et al, while classified as “non-luminal, non-basal” by Shi et al [ 46 ]. These non-luminal, non-basal cell lines expressed epithelium to mesenchyme transition markers and do not express E-cadherin.…”
Section: Mibc Molecular Subtypes As Biomarkers For Ccrt Responsementioning
confidence: 99%
See 2 more Smart Citations
“…A prevalent nonsense mutation is the Q555* with additional partial deletion of the IDR. This mutation site has been identi ed as an APOBEC3 hotspot (20). Other variants, like the moderately frequent Q333*, lack both IDR and JmjC and could potentially impair TPR8 functionality.…”
Section: Discussionmentioning
confidence: 99%